Model Antrian Servis Handphone Menggunakan Petri Net dan Aljabar Max-Plus - Afif, Ahmad (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
The development of information and communication technology has made communication unlimited by distance and time. One of the latest information and communication technologies that has been developed is handphones. People's dependence on handphones cannot be prevented because of the high activity of handphones, which used to be just a more complex means of communication nowadays, that is, as a media of information and help learning up to work. Problems arise when the handphones are damaged. Consumers' ignorance of service procedures and wait times for handphone service has caused consumers to be lazy with handphone services. In order to solve the problems that occurred, built a model petri net that describes the handphone service frontline with the approach of algebra modeling max-plus to determine the length of each consumer performing the frontline and time arrival of every consumer leaving the service. Petri net model on the system of handphone services there are 9 places and 11 transitions. Whereas the results of modeling the max-plus algebra obtained the matrix equation to estimate the service time and the duration of the process service handphone service until completed.